Defense Diplomacy between Indonesia and Vietnam in Resolving EEZ Disputes - Maramis, Raul Redemtus; Swastanto, Yoedhi; Anwar, Syaiful (PT FORMOSA CENDEKIA GLOBAL, 2024)
Indonesia is a maritime country that has a vast sea area, most of Indonesia's territory consists of waters and the rest of the land. Indonesia's vast waters are directly bordered by ten neighboring countries, namely: India, Singapore, Malaysia, Thailand, Vietnam, Philippines, Palau, Australia, Timor Leste and Papua New Guinea. This of course often causes problems where the condition of sea areas that do not have boundary markers such as land boundaries is often violated by other countries, including claims made by other countries against Indonesia's marine territory, especially the Exclusive Economic Zone (EEZ) area, one of the conflicts that arose related to the struggle for marine territory was the conflict between Indonesia and Vietnam. This research uses a qualitative analysis research method, which prioritizes data collection through interviews and a comprehensive literature study. With this, the territorial issues between Indonesia and Vietnam will be comprehensively described so that the role of Defense Diplomacy can be seen in the process of resolving EEZ disputes.